2007
DOI: 10.1111/j.1365-2672.2006.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amine production in grass, maize and total mixed ration silages inoculated with Lactobacillus casei or Lactobacillus buchneri

Abstract: Aims:  To investigate the effects of inoculating Lactobacillus casei or Lacobacillus buchneri on the production of biogenic amines (BA) in silage. Methods and Results:  Wilted festulolium (Lolium perenne × Festuca pratensis), whole crop maize or a total mixed ration, consisting of wet brewer grains, lucerne hay, cracked maize, sugarbeet pulp, soyabean meal and molasses, was ensiled with or without the inoculation of either L. casei (>106 CFU g−1) or L. buchneri (>106 CFU g−1). Silages were opened after 60 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
5
29
2
Order By: Relevance
“…The use of biological additive was not shown to affect the content of BA. This finding contrasted with the results of Nishino et al [5], who stated that biological additives containing Lactobacillus casei can reduce the content of BA in silage. However, these results were obtained in silage of festulolia and maize.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The use of biological additive was not shown to affect the content of BA. This finding contrasted with the results of Nishino et al [5], who stated that biological additives containing Lactobacillus casei can reduce the content of BA in silage. However, these results were obtained in silage of festulolia and maize.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be the result of a low content of dry matter of ensiling biomass. Nishino et al [5] listed the content of histamine up to 195 mg·kg −1 in untreated grass silage. On the other hand, they mentioned that silage treated with biological additives reduced its content only by 10.3 to 18.9 mg·kg −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. casei decreased the occurrence of histamine, tyramine, putrescine and cadaverine. L. buchenri reduced only putrescine and histamine [20]. In contrast to these results, we observed the occurrence of histamine to be highest for the biological treatment.…”
Section: Resultscontrasting
confidence: 55%
“…The reduced DMI with Lactisil Maize may have resulted from the extensive fermentation and greater silage end-products (McAllister et al, 1998;Buxton et al, 2003). Moreover, Nishino et al (2007) reported increased concentrations of biogenic amines (tyramine and putrescine) in maize silage treated with L. buchneri, which can limit DMI (Lingaas & Tveit, 1992). The reduced milk yield (P <0.01) could be attributed to a decreased net energy intake due to the lower DMI in cows fed diets containing Lactisil Maize-inoculated silage.…”
Section: Resultsmentioning
confidence: 99%